Ketahanan dan Kulturabilitas Cronobacter Sakazakii terhadap Stres Kering pada Simulasi Proses Pengeringan - Siti Nurjanah; Ratna Nurmalita Sari; Ratih Dewanti-Hariyadi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2017)
Cronobacter sakazakii is an opportunistic pathogen that has been isolated from several dried food products and reported can survive in dry conditions. Survival on dry stress can be observed using microscopy due to losses of their culturability in the medium. This study aimed to observe the survival and culturability of C. sakazakii on dry stress and ability to recover their culturability or resuscitation. This research was carried out in 3 steps: drying cells by desiccation, survival cell enumeration, and resuscitation. The bacteria used were two isolates Green fluorescence protein (pGFPuv) mutants of C. sakazakii, namely E2 and Yrt2a, that have ampicillin resistance and similar growth pattern with their wild-type. Desiccation was conducted by placed bacterial cells in incubator at 30, 35, 400 and 500C for 2 hours and air-drying stored at 210C for 72 hours. The culture able cells were enumerated on tryptone soy agar (TSA) and total cells include non-culturable cells were enumerated using fluorescence microscopy. Both of C. sakazakii isolates can survive for all of treatment. Total cells of E2 and Yrt2a decreased 2-3 and 4-5 log cells respectively. Both of isolates loss their ability to grow on medium, however suplementation the medium growth using pyruvate can resuscitate their cells and recover their culturability. Resuscitation of C. sakazakii cells might be as potential risk for increasing bacterial contaminant in food.